2013
DOI: 10.1053/j.gastro.2013.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Activated Pancreatic Stellate Cells Sequester CD8+ T Cells to Reduce Their Infiltration of the Juxtatumoral Compartment of Pancreatic Ductal Adenocarcinoma

Abstract: Background & Aims Pancreatic ductal adenocarcinoma (PDAC) is characterized by a prominent desmoplastic microenvironment that contains many different immune cells. Activated pancreatic stellate cells (PSCs) contribute to the desmoplasia. We investigated whether distinct stromal compartments are differentially infiltrated by different types of immune cells. Method We used tissue microarray analysis to compare immune cell infiltration of different pancreatico-biliary diseased tissues (PDAC, ampullary carcinoma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
429
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 459 publications
(454 citation statements)
references
References 37 publications
15
429
0
Order By: Relevance
“…T-cell infiltrate around cancer cells was correlated with improved survival after surgery, suggesting this immune reaction against cancer cells directly affects the clinical outcome [89]. This study clarified the detailed mechanism of immunosuppression by PSCs using a KPC mouse model.…”
Section: Modulation Of the Immune System In Pancreatic Cancermentioning
confidence: 73%
“…T-cell infiltrate around cancer cells was correlated with improved survival after surgery, suggesting this immune reaction against cancer cells directly affects the clinical outcome [89]. This study clarified the detailed mechanism of immunosuppression by PSCs using a KPC mouse model.…”
Section: Modulation Of the Immune System In Pancreatic Cancermentioning
confidence: 73%
“…PSCs have an important role in mediating the immunosuppressive microenvironment in PDAC by promoting proliferation and activation of MDSCs via secreting cytokines and VEGF, impairing the survival of T cells, recruiting Treg and sequestering CTLs via CXCL12/CXCR2, and CXCL12/CXCR4, respectively, impeding their contact with tumour cells [107][108][109]. Therefore, T-lymphocytes were shown to surround the pancreatic lesions and found more frequently in the fibrotic interstitial tissue than in the intraepithelial area of the PDAC [109].…”
Section: Pancreatic Stellate Cellsmentioning
confidence: 99%
“…Therefore, T-lymphocytes were shown to surround the pancreatic lesions and found more frequently in the fibrotic interstitial tissue than in the intraepithelial area of the PDAC [109]. PSCs release IL-33 to activate mast cells to produce pro-inflammatory cytokine, MMPs production promoting PDAC progression [91].…”
Section: Pancreatic Stellate Cellsmentioning
confidence: 99%
“…40,41 Higher levels of CD8 positive T-cell infiltration have been shown to correlate with a better survival, 40,41 while macrophage and neutrophil infiltration as well as high levels of MDSCs have been reported to be associated with poor survival. 40 The infiltration of MDSCs in PDAC tissue leads to the establishment of antigen-specific T-cell tolerance, which might enable cancer cells to escape from immune surveillance.…”
Section: Immune Cellsmentioning
confidence: 99%
“…44 It has been reported that PSCs negatively modulate immune responses via reducing the migration of CD8 positive T-cells to cancer cells in human PDAC and the KPC mouse model of pancreatic cancer. 41 Additionally, PSCs have been shown to activate mast cells in vitro promoting tryptase and IL13 release from the latter. These mast cell-derived factors have been shown to stimulate cancer cell proliferation.…”
Section: Immune Cellsmentioning
confidence: 99%